Analysis of Girder Deflection in a Simulated Bridge Using SAP 2000: Study Case of Nongsa Pura Bridge - Immanuel, Gabriel; Irfan Rifai, Andri; Savitri, Amanatullah; Prasetijo, Joewono (Journal Research of Social Science, Economics, and Management, 2024)
Within structural engineering, bridges demonstrate how the practical import of scientific hypotheses becomes clear to humanity. Engineers use computer simulations and models to anticipate how the bridge will react under various stresses and what its response is likely given all sorts of environments over its life span. The construction of the Nongsa Pura Bridge in Batam, which showcases cutting-edge civil engineering accomplishments customized to local requirements, represents a critical turning point in the region's infrastructure improvement. This paper aims to analyze the deflection of a Nongsa Pura Planning Simulation using SAP2000 software. This research uses secondary data and the author's assumptions as necessary data to design a bridge. The results of this research are deflection values for the main girder, transverse girder, and longitudinal girder. In the main girder, the most considerable deflection value is 0,0778724 m. In contrast, in the transverse girder, the most considerable deflection value is 0,034118 m, and the longitudinal beam has the most considerable deflection value of 0,077809 m.